Contemporary Reassessment of Punishment in Islamic and Secular Law: A Comparative Study of Justice and Penal Philosophy - Anis Mashdurohatun; Eid Abed Alhaleem Maslat Harahsheh; Muhammad Irwan Datuiding; Abun Hasbulloh Syambas; Prasetiyo Adhi Wibowo (MILRev: Metro Islamic Law Review, 2026)
This study offers a contemporary reassessment of punishment in Islamic Sharia and secular legal systems by comparatively examining their classifications, objectives, and underlying penal philosophies. While both frameworks seek to deter crime, uphold justice, and preserve social order, they diverge significantly in epistemological foundations, moral orientation, and modes of legal authority. Employing a qualitative comparative legal approach, this research integrates classical Islamic jurisprudence with contemporary statutory regulations and judicial practices. The analysis moves beyond doctrinal exposition to address current challenges in crime prevention, legal objectivity, proportionality, and the role of state authority in administering punishment. Particular attention is given to the ethical coherence and legitimacy of each system in responding to modern social complexities. The findings reveal that Islamic Sharia—especially through its taʿzīr framework—offers a principled yet flexible penal paradigm that balances deterrence, moral reform, and restorative considerations. Its emphasis on proportionality, judicial discretion, and ethical responsibility reflects a holistic vision of justice consistent with the objectives of the Maqāṣid al-Sharia. Conversely, contemporary secular legal systems increasingly prioritize rehabilitation and utilitarian efficiency but often encounter structural challenges, including sentencing disparities, systemic bias, and susceptibility to political or socioeconomic interests. This study contributes academically by enriching comparative penal theory through an integrative ethical analysis of Sharia and secular models. It demonstrates that Sharia’s justice-oriented framework provides valuable normative insights for contemporary penal reform, particularly in enhancing fairness, accountability, and moral balance within modern criminal justice systems.